Ergonomic analysis in the bagging of gran equipment: unsuitability of the work stations. - Soares, Marcelo M.; Jacobs, Karen; Mariño, Suzi; Lemos, Leandro (Work)
This analysis was performed in the industry for bagging grain (granular urea) nitrogen fertilizer factory in order to raise the causes of accidents on the operators. Data collection through direct observation and interviews done with the managers and operators have identified the causes of accidents. The results show an evident fact: the working conditions of bagging grain cause embarrassment to the employee, as well as the emergence of pathophysiology due to overload, then the problems of work organization involving mainly equipment, tools and accessories inadequate. At the end of this work are related suggestions, which has as its goal the reduction or even elimination of accidents involving operators bagging grain.